Pre-Service Teachers' Experience in Thai EFL Classrooms - Denny Maschuri (Barkah Publishing, 2025)
This study investigates the experiences of Indonesian pre-service teachers in implementing Task-Based Language Teaching (TBLT) and Communicative Language Teaching (CLT) in Thai EFL classrooms. Using a qualitative descriptive method, data were obtained through semi-structured interviews with six purposively selected participants. The findings reveal that participants applied TBLT by designing authentic tasks such as role-plays and problem-solving activities, while CLT was implemented through interactive group discussions and communicative games to enhance students’ communicative competence. Challenges encountered included students’ low English proficiency, cultural norms discouraging public speaking, and limited teaching resources. Participants addressed these issues by simplifying instructions, incorporating visual aids, and adapting activities to available resources. The study concludes that TBLT and CLT can be effectively adapted in under-resourced Thai EFL contexts when supported by scaffolding, cultural sensitivity, and context-responsive pedagogy, contributing to the participants’ professional growth in adaptability, intercultural communication, and classroom management.